Pendampingan Peningkatan Kompetensi Pedagogik Guru SD Sekabupaten Barru Dalam Mengembangkan Modul Ajar - Usman, Usman; Amran, Muhammad; Syarif, Naufal Qadri; Iyan, Iyan; Ilmi, Nur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This community service activity aims to improve the pedagogical competence of elementary school teachers throughout Barru Regency in developing teaching modules that are in accordance with the curriculum and local needs. This community service activity was carried out on 3-7 July 20024. The methods used in this activity include socialization, formation of mentoring groups, workshops, technical guidance, and ongoing evaluation. The results of this mentoring activity showed a significant increase in the pedagogical competence of teachers, especially in terms of compiling and using teaching modules in the classroom. As many as 80% of participants reported increased skills in designing more systematic, relevant, and applicable modules. The conclusion of this community service activity is that the mentoring program succeeded in improving the ability of teachers in developing teaching modules. This success has a long-term positive impact on improving the quality of education in Barru Regency.